Secondary erythrocytosis following drugs used in rifampicin/multidrug-resistant tuberculosis: a retrospective cohort study - Henok Woldu; Sirak Tesfamariam; Mulugeta Russom; Amon Solomon Ghebrenegus; Ephrem Fisseha; Gebremeskel Belai (BMJ Open Respiratory Research)
Background Multidrug-resistant tuberculosis (MDR-TB) drugs have never been associated with erythrocytosis. In Eritrea, however, several cases of incident erythrocytosis had been observed in the MDR-TB hospital. This study was aimed at exploring the association between MDR-TB drugs and secondary erythrocytosis, characterising the cases, and identifying other possible risk factors.Methods A retrospective cohort study was conducted in Merhano National Referral MDR-TB hospital. Data were extracted from physically available clinical cards and laboratory results collected longitudinally between 23 June 2011 and 17 January 2021. Initially, univariate descriptive statistics (frequency, mean (SD), median (IQR) and range) were used as appropriate. Then, χ2 or Fisher χ2 test, and bivariate and/or multivariate Cox proportional hazard model were used to identify the predictors of incident erythrocytosis. All statistical analyses were conducted using R, and a two-sided alpha 0.05 was used to determine the statistical significance.Results A total of 257 patients’ medical cards were screened, and 219 were eligible for further analysis. The median age of the patients was 38 years (range: 13–90 years) and 54.8% were males. During the follow-up time, 31 (14.2%) patients developed secondary erythrocytosis yielding an incidence rate of 7.8 cases per 1000 person-months. On average, the median time to onset of the event was found to be 5-months (range: 1–24 months). Males were more likely to develop the event than females (adjusted HR=7.13, 95% CI=1.66 to 30.53), and as body weight increases by 1 kg, the likelihood of developing secondary erythrocytosis was found to increase by 7% (adjusted HR=1.07, 95% CI=1.03 to 1.10). Moreover, all cases of secondary erythrocytosis were found to be possibly associated with the MDR-TB drugs.Conclusion The authors hypothesised that the incident erythrocytosis is possibly be associated with MDR-TB drugs, and further studies are required to substantiate this finding.